2023
DOI: 10.3389/fnins.2023.1109510
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in the field of the gut-brain interaction: Functional dyspepsia in the spotlight – An integrated bibliometric and science mapping approach

Abstract: ObjectivesThis study aims to perform a bibliometric analysis of functional dyspepsia (FD), which includes visualizing bibliographic information, in order to identify prevailing study themes, topics of interest, contributing journals, countries, institutions, and authors as well as co-citation patterns.MethodsThe Web of Science™ Core Collection Database was used to retrieve all peer-reviewed scientific publications related to FD research. The validated search terms were entered into the “title” and “author keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 301 publications
0
5
0
Order By: Relevance
“…Visceral hypersensitivity is a crucial factor in functional gastrointestinal disorder syndrome, greatly influencing the occurrence and severity of symptoms. This is due to an abnormal mucosal immune response activation in relation to the level of inflammatory response and the close proximity of immune cells and sensory neurons [ 105 ]. There are numerous factors related to visceral hypersensitivity and signal transduction, such as the expression of cytokines, the secretion of corticosterone, the release of SCFAs, and microbial metabolites [ 106 ].…”
Section: Relationship Between Intestinal Flora and Fdmentioning
confidence: 99%
“…Visceral hypersensitivity is a crucial factor in functional gastrointestinal disorder syndrome, greatly influencing the occurrence and severity of symptoms. This is due to an abnormal mucosal immune response activation in relation to the level of inflammatory response and the close proximity of immune cells and sensory neurons [ 105 ]. There are numerous factors related to visceral hypersensitivity and signal transduction, such as the expression of cytokines, the secretion of corticosterone, the release of SCFAs, and microbial metabolites [ 106 ].…”
Section: Relationship Between Intestinal Flora and Fdmentioning
confidence: 99%
“…Additionally, data sharing enables the pooling of information from multiple sources, enhancing the statistical power and generalizability of research findings. Standardized outcome measures and multicenter studies help generate robust evidence, establishing best practices for managing autoimmune gastritis symptoms [ 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…The analysis also underlines the diversity of sources from which volleyball training research is published, covering a wide range of aspects, from physical to psychological. The identification of these key sources provides important insights for researchers and practitioners and creates a strong basis to further explore this topic in a bibliometric context (Zhang et al, 2023), as well as opportunities for further collaboration and research. The source analysis also confirmed that in academia, the reputation of particular journals and conferences can have a major impact on the recognition and number of citations for research (Zhang et al, 2019).…”
Section: Countrymentioning
confidence: 99%